2013
DOI: 10.1186/1743-422x-10-314
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive profiling of Epstein-Barr virus-encoded miRNA species associated with specific latency types in tumor cells

Abstract: BackgroundEpstein-Barr virus (EBV) is an etiological cause of many human lymphocytic and epithelial malignancies. EBV expresses different genes that are associated with three latency types. To date, as many as 44 EBV-encoded miRNA species have been found, but their comprehensive profiles in the three types of latent infection that are associated with various types of tumors are not well documented.MethodsIn the present study, we utilized poly (A)-tailed quantitative real-time RT-PCR in combination with microar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 60 publications
1
36
0
Order By: Relevance
“…3D). Unlike typical pre-miRNAs, pre-miR-BART-18 has been reported to give rise to both abundant 5′ (5p) and 3′ derivate (3p) miRNAs, depending on cellular context (39,42,43). We confirmed that expression of pre-miR-BART-18 gives rise to approximately equally abundant 5p and 3p derivatives in HEK293T cells (Fig.…”
Section: Significancesupporting
confidence: 77%
“…3D). Unlike typical pre-miRNAs, pre-miR-BART-18 has been reported to give rise to both abundant 5′ (5p) and 3′ derivate (3p) miRNAs, depending on cellular context (39,42,43). We confirmed that expression of pre-miR-BART-18 gives rise to approximately equally abundant 5p and 3p derivatives in HEK293T cells (Fig.…”
Section: Significancesupporting
confidence: 77%
“…Silencing of endogenous EBV-miR-BART7-3p attenuates the EMT and cell migration in EBV-positive NPC cells EBV-miR-BARTs were preferentially expressed in EBV-infected epithelial cells, 25,39,40 so we replicated our experiments in the EBV-positive NPC cell line to validate our findings. NPC EBVpositive cell lines (C666-1-EBV, HONE1-EBV and HK1-EBV) were initially confirmed to express EBV-miR-BART7-3p at a similar level to CNE1-BART7-3P cells, 5-8F-BART7-3p cells and NPC tissues (Supplementary Figure S6a).…”
Section: Resultsmentioning
confidence: 53%
“…This virus expresses more than 40 mature miRNAs in latently infected cells. Of them, some miRNAs encoded by BamH I-A rightward transcripts (BARTs) of EBV are disclosed to be highly expressed in some cancers such as gastric cancer, 23 lymphomas 24 and NPC, [25][26][27] contributing to viral latency, [28][29][30] host cell survival, 30,31 immune escape, 32 cell proliferation, 33 cell apoptosis 31,34 and cancer metabolism. 35 However, there have been few reports of the relationship between viral miRNAs and EMT in cancer to date.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to hosts, a number of viruses, including WNV (3), bovine leukemia virus (23), Epstein-Barr virus (24), herpesviruses (25), and others (26), encode miRNAs, which regulate host and viral genes to enhance viral replication. Viruses can also recruit cellular miRNAs to facilitate their replication.…”
mentioning
confidence: 99%